Design of Internet of Things (IoT)-Based Control System on a Hybrid Drying Machine for Sengon Wood Pallets - Yefri Chan; Suzuki Sofyan (The University of Lampung, 2026)
This study aims to design and build a sengon wood pallet drying system with an Internet of Things (IoT) based system as a monitoring and control of drying parameters such as temperature, humidity and reduction of wood mass during the drying process. Drying of sengon wood pallet samples using a combined infrared-hot air method was carried out at temperatures of 65, 75 and 85 °C and at an air velocity of 2m/s. Observation involved wood moisture content, core temperature, chamber temperatures, and air humidity which were recorded every 10 min interval during drying process. Results showed that the IoT system can function well and make the sengon wood pallet drying process monitored and controlled remotely. Wood pallet sample reached optimum conditions with moisture content of 19% at a temperature test of 85 °C. At this condition average core temperature of sengon wood pallets of 67.05 °C was recorded and a drying time of 180 min was required. The longest drying time was at a test temperature of 65 °C, with an average core temperature of 56.37 °C, and a drying time of 370 min.